Development and Improvement of Methods to Disinfect Raw Beef Using Calcium Hydroxide–Ethanol–Lactate-Based Food Disinfectant for Safe Consumption - Kayali, Ahmad Yaman; Yamashita, Yasuharu; Kawakami, Hiroo; Kiyota, Hironori; Ozawa, Jo; Nishibuchi, Mitsuaki (Frontiers in Microbiology, 2020)
The enterohemorrhagic Escherichia coli (EHEC) group is responsible for outbreaks and sporadic cases around the world annually. EHEC produces a potent protein known as Shiga toxin in the human intestine causing mild to bloody diarrhea. Some cases of EHEC infections may develop life-threatening symptoms, which may lead to human death. It also has other virulent factors that enable the EHEC cells to adhere to a target tissue and invade to some extent to crave more nutrition and escape the external extreme conditions, such as disinfection treatment. For those reasons, beef is not permitted for raw consumption unless guaranteed free of harmful bacteria, including EHEC, or the invading bacterial cells are completely removed or reduced to a safe level. A heat treatment that guarantees a sufficiently high temperature to reach inside the tissue of meat through the surface was established in Japan. This treatment may allow the core part of the meat to be consumed raw. However, it seemed to have some limitations. We aimed at developing a disinfection method with, hypothetically, nutrition-preserving property that is equivalent to the heat treatment or even superior. A combination of calcium hydroxide–ethanol–lactate-based food disinfectant and two proposed physical sterilization methods, assisted with microbial detection methods, exerted sufficient bactericidal activities against EHEC cells adhering to and/or invading the beef. These physical methods showed great usefulness in disinfecting fresh full-size boneless Round-beef of around 12 kg including fat on the outside. The first method applied a commercially available wide-drum washing machine (WM method) while the second method applied a specially designed plastic bag and a commercially available vibration machine (VV method). After trimming out the fat and the denatured surface of the beef (1 cm from the surface), the remaining meat mass showed no signs of denaturation and a significant reduction of viable EHEC cells by a factor of >104 CFU/ml. However, in the WM method, the disinfection process required a large amount of the disinfectant (150 L). The improved method, VV method, implemented a system that consumes a smaller amount of the disinfectant (50 L) while ensuring the targeted disinfection power degree.